The UNDP Accelerator Labs enter a year of maturity: let a thousand flowers bloom! - Annual report 2022 - and UNDP accelerator labs (UNDP, 2022)
The UNDP Accelerator Labs were designed as an agile and dynamic Network to allow communication and information transfer between 91 Accelerator Labs in 115 countries, and with the global innovation ecosystem, UNDP as a whole, and thousands of partners including grassroots innovators and their communities. The accumulated knowledge of this Network creates new pathways to the solutions that hold the key to sustainable development problems. What it looked like and how it unfolded last year will be illuminated in this annual report: The UNDP Accelerator Labs enter a year of maturity: let a thousand flowers bloom!